Cover Feature: Rational Control of Off‐State Heterogeneity in a Photoswitchable Fluorescent Protein Provides Switching Contrast Enhancement (ChemPhysChem 19/2022). Issue 19 (6th October 2022) - Adam, Virgile; Hadjidemetriou, Kyprianos; Jensen, Nickels; Shoeman, Robert L.; Woodhouse, Joyce; Aquila, Andrew; Banneville, Anne‐Sophie; Barends, Thomas R. M.; Bezchastnov, Victor; Boutet, Sébastien; Byrdin, Martin; Cammarata, Marco; et al.
Abstract : The Cover Feature displays a comparison of chromophore conformations in the X‐ray crystal structures of the reversibly photoswitchable fluorescent protein rsEGFP2 in its on state (green) and its V151L (purple) and V151A (yellow) variants in their off states. The latter displays an increased photoswitching contrast, as indicated by the displayed switching kinetics. Cover design by Virgile ADAM. More information can be found in the Research Article by Dominique Bourgeois, Martin Weik and co‐workers .